2020
DOI: 10.3390/ani10010083
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Cu Supplementation of Late-Gestating and Lactating Iberian Red Deer Hinds Fed a Balanced Diet Reduces Somatic Cell Count and Modifies Mineral Profile of Milk

Abstract: This study describes the effects that Cu supplementation of late-gestating and lactating females (hinds) of Iberian red deer fed a balanced diet have on milk production, composition, and somatic cell count (SCC). Experimental hinds (n = 9) were subcutaneously injected every 42 days with Cu (0.83 mg Cu/kg body weight) from day 202 of gestation until the end of lactation (week 18). Control hinds (n = 8) were injected with a physiological saline solution with the same volume and at the same frequency as the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Table 1 presents the mean values and lactation period effect for daily milk production (DMP) and the gross composition of the raw milk collected from five individual red deer hinds over the period from May to October 2016. DMP decreased significantly ( p < 0.000) during lactation, with mean values similar to those reported by other authors at the same lactations times [ 29 , 33 ]. Mean red deer milk values were 10.4, 7.1, 5.1, 4.3 and 24.2% for fat, protein, CN, lactose and DM, respectively.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Table 1 presents the mean values and lactation period effect for daily milk production (DMP) and the gross composition of the raw milk collected from five individual red deer hinds over the period from May to October 2016. DMP decreased significantly ( p < 0.000) during lactation, with mean values similar to those reported by other authors at the same lactations times [ 29 , 33 ]. Mean red deer milk values were 10.4, 7.1, 5.1, 4.3 and 24.2% for fat, protein, CN, lactose and DM, respectively.…”
Section: Resultssupporting
confidence: 89%
“…Regarding the somatic cell count, the data revealed that animals had good sanitary conditions during the study period ( Table 3 ). Studies about SCC in red deer milk are scarce and limited to a few individuals [ 24 , 33 ]. During the interval being studied, an increase in SCC at the end was not observed, unlike the slight increase noticed for a similar period by Pérez Serrano [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations